Game-Based Learning and Multimodal Media in English Vocabulary Learning: A Systematic Literature Review - Tristania Handikaningtyas; Saida Ulfa; Taufik Ikhsan Slamet; Made Duananda Kartika Degeng (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2025)
This systematic literature review synthesizes empirical evidence from 2021–2025 on the integration of Game-Based Learning (GBL) and multimodal media to enhance English vocabulary acquisition in EFL contexts. The study aims to evaluate instructional effectiveness, identify synergistic benefits, and examine implementation challenges. Following the PRISMA 2020 protocol, we systematically searched Scopus, Web of Science, ERIC, ScienceDirect, and Google Scholar. Twelve peer-reviewed studies meeting stringent eligibility criteria underwent qualitative synthesis. Findings consistently demonstrate that GBL significantly improves vocabulary acquisition, learner motivation, and engagement compared to traditional methods. Multimodal instruction (integrating text, audio, and visuals) enhances vocabulary retention and depth of processing by supporting dual coding and reducing cognitive load. Crucially, integrated approaches that embed multimodal elements within game mechanics yield synergistic gains in cognitive, affective, and social engagement. However, successful implementation faces barriers, including over-reliance on translation-based methods and varying teacher readiness in digital-pedagogical competencies. The review concludes that combining GBL with multimodal design principles offers a powerful, engaging framework for vocabulary instruction. Future research should prioritize longitudinal studies on retention, design-based development of adaptable resources, and implementation science models to support teacher professional development in diverse educational settings.